Enhancing Reading Abilities: Exploring the Interrelationships among Speed, Critical, and Creative Reading through Classroom-Based Action Research - Wiwiek Afifah; Soeharto Soeharto; Tri Rina Budiwati; Zanuwar Hakim Atmantika (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
When students have good level of speed, critical and creative reading abilities, they will easily understand scientific knowledge and able to understand big volume of reading sources. However, most of teaching reading are dominated with conventional methods emphasizing on reading with question-and-answer. For the reasons, this study explores how do reading skills for speed, critical, and creative interrelate to one another, what specific techniques can be applied to enhance the level of students’ speed, critical, and creative reading abilities, and how were the three readings skills interrelation and connected to Foreign Language Learning theories. The research design was classroom action research with the participants of 35 students from English Literature Study Program. Two types of data: quantitative and qualitative were gained by using test and non-test. They were analysed descriptively by using interactive data analysis consisting of reduction, presentation, and verification. The data showed that students’ speed, critical, and creative reading abilities were still under standard but after the treatments, they made improvement. Their speed, critical and creative reading abilities reached standard scores. There is interrelation among speed, critical, and creative reading abilities. While integrating them in the reading class, students’ level of reading skills enhanced. They could employ speed-reading strategies to quickly comprehend the texts before engaging in critical and creative reading. In critical reading, students could optimize their ability in questioning, problematizing and not passively follow the information given by the authors. Yet, students can read the text by optimizing their imagination in understanding the text information.